Weight Gain During Treatment of Bipolar Disorder (BD)—Facts and Therapeutic Options - Mangge, Harald; Bengesser, Susanne; Dalkner, Nina; Birner, Armin; Fellendorf, Frederike; Platzer, Martina; Queissner, Robert; Pilz, Rene; Maget, Alexander; Reininghaus, Bernd; Hamm, Carlo; Bauer, Konstantin; et al. (Frontiers in Nutrition, 2019)
Bipolar disorder (BPD) is a mood disorder, which is characterized by alternating affective states, namely (hypo)mania, depression and euthymia. Evidence is growing that BPD has indeed a biologic substrate characterized by chronic inflammation, oxidative stress and disturbed energy metabolism. Apart from this, there is obviously a hereditary component of this disease with multi-genetic factors. Most probably a susceptibility threshold favours the outbreak of clinical disease after a cascade of stress events that remain to be elucidated in more detail. Evidence is also growing that weak points in brain energy metabolism contribute to outbreak and severity of BPD. Conventional psychopharmacologic therapy must be reassessed under the aspects of weight cycling and development of central obesity as a deterioration factor for a worse clinical course leading to early cardiovascular events in BPD subgroups.